Electrical engineering - Johnson, Jame H. (International Texbook, 1965)
This streamlined review gets you solving problems quickly to measure your readiness for the PE exam. After each solution, a pointer to further review is provided if you need it. Solutions to multiple-choice problems include explanations of plausible wrong answers as well as the correct ones.